2018
DOI: 10.31729/jnma.3760
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Indications of Cesarean Section in a Community Hospital of Western Region of Nepal

Abstract: Introduction: Cesarean section is one of the common obstetric procedures done when the childbirth is not anticipated to occur by the normal vaginal delivery. There has been increased rate of cesarean section globally as well as in our country in recent decades. Methods: This descriptive cross-sectional study has been carried out by reviewing a year of data from maternity ward of Paschimanchal Community Hospital, Prithvi Chowk, Pokhara. The total number of delivery, their modes either vaginal or ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
2
11
2
1
Order By: Relevance
“…The most common indication for CS in community hospital in Pokhara is oligohydromnos, 23.56%. 5 However our study revealed that the most common indication in our centre was previous caesarean section which was similar to the study done in Kathmandu Medical College (KMC) by Apurwa Prasad et al 6 Current medical literature suggests that 60-80% of women can achieve vaginal delivery. 7 Sharma et al in their studies found indication of repeat elective caesarean section was refusal of trial of scar, when the women were told about risk associated with trial of scar like uterine rupture, scar dehiscence and bleeding due to adherent placenta.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The most common indication for CS in community hospital in Pokhara is oligohydromnos, 23.56%. 5 However our study revealed that the most common indication in our centre was previous caesarean section which was similar to the study done in Kathmandu Medical College (KMC) by Apurwa Prasad et al 6 Current medical literature suggests that 60-80% of women can achieve vaginal delivery. 7 Sharma et al in their studies found indication of repeat elective caesarean section was refusal of trial of scar, when the women were told about risk associated with trial of scar like uterine rupture, scar dehiscence and bleeding due to adherent placenta.…”
Section: Discussionsupporting
confidence: 87%
“…Similar study done at a community hospital of western region of Nepal found CS rate as 63.27%, which was quite high as compared to our study. 5 The rate of CS at our hospital was also slightly higher than other district level hospitals or Comprehensive Emergency Obstetric and Neonatal Care(CEONC) center. This may be because our hospital is located in Pokhara, which is among of major cities in Nepal.…”
Section: Discussionmentioning
confidence: 63%
“…Delivery is a completely natural process that requires preventive and supportive measures. Normal delivery applies to mothers who are unable to perform it, otherwise, a cesarean section may be used in cases where childbirth is not possible or if it may pose risks to the mother and infant (1). Over the past few decades, cesarean sections have increased dramatically around the world, causing concern for public health officials (2).…”
Section: Introductionmentioning
confidence: 99%
“…Of the total births in Nepal in 2016, CSs accounted for 9%, but with large discrepancies depending on women's educational level (5% among women with no education vs. 20% among women with secondary level education), wealth (2% among women in the lowest wealth quantile vs. 28% in the highest), and type of facility (12% in public facilities vs. 35% in private) [33]. Hence, many researchers argue that there might be an overuse of CS in some facilities in Nepal and that this needs to be investigated in further detail [9,34,35].…”
mentioning
confidence: 99%
“…Most previous research to assess accuracy of CS indications, in Nepal as well as other low-resource settings, have been based at one facility and included relatively small sample sizes [5,6,8,12,34]. It has been reported that the majority of stillbirths and cases of neonatal encephalopathy in Nepal are associated with intrapartum hypoxia and suboptimal care [36], and that there is a lack of proper FHRM and partograph use in Nepali hospitals [27].…”
mentioning
confidence: 99%